Creutzfeldt-Jakob disease: a systematic review of global incidence, prevalence, infectivity, and incubation. Issue 1 (January 2020) - Uttley, Lesley; Carroll, Christopher; Wong, Ruth; Hilton, David A; Stevenson, Matt
Summary: Creutzfeldt-Jakob disease (CJD) is a fatal disease presenting with rapidly progressive dementia, and most patients die within a year of clinical onset. CJD poses a potential risk of iatrogenic transmission, as it can incubate asymptomatically in humans for decades before becoming clinically apparent. In this Review, we sought evidence to understand the current iatrogenic risk of CJD to public health by examining global evidence on all forms of CJD, including clinical incidence and prevalence of subclinical disease. We found that although CJD, particularly iatrogenic CJD, is rare, the incidence of sporadic CJD is increasing. Incubation periods as long as 40 years have been observed, and all genotypes have now been shown to be susceptible to CJD. Clinicians and surveillance programmes should maintain awareness of CJD to mitigate future incidences of its transmission. Awareness is particularly relevant for sporadic CJD, which occurs in older people in whom clinical presentation could resemble rapidly developing dementia.